PENERAPAN METODE DEMONSTRASI UNTUK MENINGKATKAN KETERAMPILAN PENGURUSAN JENAZAH PADA SISWA KELAS IX MADRASAH TSANAWIYAH TARBIYAH MAZNIAH KOTA JAMBI - Marisa; Nurul Hazairin, Indah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the low understanding and skills of students in the practice of handling corpses, which has become an issue in Islamic Religious Education. This is evident from the Pre-Cycle results, which show that the majority of students have not yet achieved learning completeness. This research aims to improve students' understanding and skills throuh the application of the demonstration method. This research is a Classroom Action Research (CAR) conducted in two cycles with a total of 13 student subjects. Each cycle consists of the stages of planning, implementation, observation, and reflection. Data collection techniques used include observation, multiple-choice tests (pre-test and post-test), and practical assessments. The research results show that there was a significant improvement in student learning outcomes. In the Pre-Cycle, student learning completeness only reached 23%. In Cycle I, it increased to 46%, but did not meet the success indicators. After improvements were made in Cycle II, student learning completeness increased to 85% and exceeded the established success criteria. Thus, it can be concluded that the application of the demonstration method is effective in improving students' understanding and skills in the practice of handling corpses.